Stimulation of adventitious root formation by the oligosaccharin OSRG at the transcriptome level. (2nd January 2020) - Larskaya, Irina; Gorshkov, Oleg; Mokshina, Natalia; Trofimova, Oksana; Mikshina, Polina; Klepikova, Anna; Gogoleva, Natalia; Gorshkova, Tatyana
ABSTRACT: Oligosaccharins, which are biologically active oligosaccharide fragments of cell wall polysaccharides, may regulate the processes of growth and development as well as the response to stress factors. We characterized the effect of the oligosaccharin that stimulates rhizogenesis (OSRG) on the gene expression profile in the course of IAA-induced formation of adventitious roots in hypocotyl explants of buckwheat ( Fagopyrum esculentum Moench.). The transcriptomes at two stages of IAA-induced root primordium formation (6 h and 24 h after induction) were compared after either treatment with auxin alone or joint treatment with auxin and OSRG. The set of differentially expressed genes indicated the special importance of oligosaccharin at the early stage of auxin-induced adventitious root formation. The list of genes with altered mRNA abundance in the presence of oligosaccharin included those, which Arabidopsis homologs encode proteins directly involved in the response to auxin as well as proteins that contribute to redox regulation, detoxification of various compounds, vesicle trafficking, and cell wall modification. The obtained results contribute to understanding the mechanism of adventitious root formation and demonstrate that OSRG is involved in fine-tuning of ROS and auxin regulatory modes involved in root development.